2015
DOI: 10.1021/acs.jafc.5b03086
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation, Identification, and Autotoxicity Effect of Allelochemicals from Rhizosphere Soils of Flue-Cured Tobacco

Abstract: Autotoxicity, defined as a deleterious allelopathic effect among individuals of the same plant species, is considered as one of the factors that contributes to replant failure. Tobacco, as an important cultured and economic crop over the world, has been often hampered by replant failure. In view of the seriousness of this problem, the allelochemicals of flue-cured tobacco and their allelopathic effects were investigated. The extracts of rhizosphere soil exhibited phytotoxic activities against Lactuca sativa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…High stability, combined with low water solubility, promotes soil retention of these compounds. In the case of tobacco, ergosta‐5‐en‐3‐ol causes a slight reduction in the root and stem lengths of its own crop . Furthermore, plants are evolving genotypes resistant to this phytotoxin due to continuous exposure.…”
Section: Chemistrymentioning
confidence: 99%
“…High stability, combined with low water solubility, promotes soil retention of these compounds. In the case of tobacco, ergosta‐5‐en‐3‐ol causes a slight reduction in the root and stem lengths of its own crop . Furthermore, plants are evolving genotypes resistant to this phytotoxin due to continuous exposure.…”
Section: Chemistrymentioning
confidence: 99%
“…The rates of dead cells in the the two compounds were 60% of the total cuticular secreta of tobacco leaf and flower (Johnson et al,1985). Recent studies indicated that β-cembrenediol played an allelochemical-affecting growth of L. sativa and tobacco itself (Ren et al, 2015). In this study, lettuce seedlings were used as a receptor to illustrate the action mechanism for the phytotoxicity of β-cembrenediol.…”
Section: Discussionmentioning
confidence: 99%
“…grade and used without purification. β-Cembrenediol was isolated according to previous procedures (Ren et al, 2015). It was characterized ( Fig.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations